2021
DOI: 10.1093/pm/pnab167
|View full text |Cite
|
Sign up to set email alerts
|

Spine-Adjusting Instrument (Impulse®) Attenuates Nociception and Modulates Oxidative Stress Markers in the Spinal Cord and Sciatic Nerve of a Rat Model of Neuropathic Pain

Abstract: Objective Oxidative stress plays an important role in neuropathic pain. Spinal manipulative therapy (SMT) can exert beneficial effects in pain outcomes in humans and animal models. SMT can also modulate oxidative stress markers in both humans and animals. We aimed to determine the effect of Impulse®-assisted SMT (ISMT) on nociception and oxidative stress biomarkers in the spinal cord and sciatic nerve of rats with neuropathic pain (NP). Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…MWL and TWL are typical behavioral tests for assessing sensory recovery after sciatic nerve injury in rats. 42 Therefore, MWL and TWL tests, it was found that one time tuina could relieve the NP caused by peripheral nerve injury. After the modeling of minor CCI, the rats were observed to chew the lower limb of the modeling side and claudication, and the behavioral test result that Tuina group and the Model group had statistical significance compared with the Sham group, the result indicates that the model is created successfully.…”
Section: Discussionmentioning
confidence: 98%
“…MWL and TWL are typical behavioral tests for assessing sensory recovery after sciatic nerve injury in rats. 42 Therefore, MWL and TWL tests, it was found that one time tuina could relieve the NP caused by peripheral nerve injury. After the modeling of minor CCI, the rats were observed to chew the lower limb of the modeling side and claudication, and the behavioral test result that Tuina group and the Model group had statistical significance compared with the Sham group, the result indicates that the model is created successfully.…”
Section: Discussionmentioning
confidence: 98%
“…The TWL is one of the classic methods to evaluate the recovery of sensory function after sciatic nerve injury in rats. It can quantitatively evaluate the sensory function recovery of injured hindlimbs (da Silva et al., 2022 ). In the present study, the sensory function gradually recovered in both the experimental and control groups, indicated by decreased TWL.…”
Section: Discussionmentioning
confidence: 99%